The use of animation video on tenth-grade students’ vocabulary achievement - Stefany Arbella Dzebeq; Agus Gunawan (TRANSBAHASA, 2020)
Vocabulary is something that very important in learning English. Relating to vocabulary, students find that it is difficult to recognize the meaning and written form. Further, there are difficulties in reading English texts. The animation video is an interested medium which expected to help and develop students’ vocabulary achievement. The research methodology in this research is quantitative, true experimental. Further, the research design is post-test only control group design. The sampling technique applied is Cluster Random Sampling, where the samples are randomly taken from the population. There are 60 samples of students and the sample classes are divided into two classes, Experimental and Control classes. Each class with 30 students. The instrument used to collect the vocabulary achievement in form of an objective test, consisting of 30 questions. The result of data are analyzed using t–test, the researcher found that Tobserved = 13,355 is higher than Ttable = 2.000 and significant (2-tailed) 0.00 than < (lower) than Alpha 0.05 that means Ho is rejected and Ha is accepted. Based on the result, it can be concluded that there is a significant effect of using animation video on tenth-grade students’ vocabulary achievement at MAN 18 JAKARTA.